ANALISIS PENGUASAAN LAHAN MENGGUNAKAN PENGINDERAAN JAUH PADA KAWASAN HUTAN PRODUKSI TETAP DI DESA KALE KO’MARA - Kristina Sara Bandangan; Naufal Naufal; Sultan Sultan; Andi Azis Abdullah; Hasanuddin Molo (Jurnal Belantara, 2023)
Land cover is one of the important data that is always changing dynamically. This study aims to determine land cover changed in 2002 and 2022; and find out the indications of land tenure on the 2021 PPTPKH Indicative Map in the Permanent Production Forest Area of the Komara Forest Group in Kale Ko'mara Village, North Polombangkeng District, Takalar Regency, South Sulawesi Province. This research was conducted from May to August 2022. The data used include primary data which consists of landsat 7 imagery in 2002 and drone’s orthophoto in 2022; secondary data consists of the digital data of the forest area, the 2021 PPTPKH Indicative Map, and the Indonesian Official Topographic Maps. Analysis data by using remote sensing approached and GIS technique such as interpretation of imagery, overlay, and tabulation.  The research showed: (1) the results of the analysis of land cover changes in 2002 and 2022 are secondary dry land forest has increased by 112.81 hectares, shrubs has decreased by 175.70 hectares, dry land agriculture has increased by 195.87 hectares, mixed dry land agriculture has decreased by 139.31 hectares, open land has increased by 2.88 hectares, and water body has increased by 3.45 hectares; (2) the results of data analysis of land tenure indications on the 2021 PPTPKH Indicative Map are being indicated not controlled and been in the indicative map is 4.75 hectares, being indicated not controlled and been outside the indicative map is 123.87 hectares, being indicated controlled and been in the indicative map is 105.50 hectares, being indicated controlled and been outside the indicative map is 126.20 hectares, it has not been identified whether there is any indication of control and been in the indicative map is 8.77 hectares, it has not been identified whether there is any indication of control and been outside the indicative map is 13.35 hectares.